Significance of tungsten disulfide on the mechanical and machining characteristics of phosphor bronze metal matrix composite - P Sangaravadivel; G Rajamurugan; Prabu Krishnasamy (Advanced Composites Letters, 2020)
The phosphor bronze (PB) is widely preferred in various engineering applications due to its high strength, toughness, fine grain size, low coefficient of friction, and better corrosion resistance. The present work is to investigate the effect of tungsten disulfide (WS 2 ) solid lubricant particle reinforcement in the phosphor bronze metal matrix composite (PBMC) through the mechanical and machining characteristics. The different variant of the composite is fabricated using stir casting technique by varying the volume percentage of WS 2 particle from 0% to10%. The prepared PBMC samples are subjected to mechanical and machining (boring and high-speed turning) characterizations. The hardness (Brinell hardness) and flexural strength of the composites are examined as per the ASTM standard. The surface roughness (Ra) of the PBMC sample is analyzed through the boring and high-speed turning operations by varying the spindle speed, feed rate, and depth of cut. The scanning electron microscope (SEM) is employed to confirm the uniform dispersion of the reinforcement particle through the microstructural analysis. The presence of WS 2 particles and other ingredients is ensured by X-ray diffraction analysis in the composites. The influence of WS 2 reinforcement particles on tool life is analyzed on the PBMC4 (PBMC with 8% WS 2 ) with the predefined machining parameters in the high-speed turning operation. The increase in WS 2 particle (0–10%) improves the hardness (11.85%) and flexural strength in PBMC4 as compared to PBMC1 (PBMC with 0% WS 2 ). At a higher spindle speed (1200 r/min), the Ra is reduced in PBMC1 as compared to 900 r/min, whereas the rest of the PBMC sample show higher surface irregularity at 1200 r/min.